2018
DOI: 10.3329/jbcps.v36i4.38182
|View full text |Cite
|
Sign up to set email alerts
|

Role of Naked Eye Single Tube Red Cell Osmotic Fragility Test (NESTROFT) in Detecting Beta-Thalassemia Trait

Abstract: Thalassemia is one of the commonest inherited diseases in Bangladesh. The birth of a thalassemic child places considerable strain, not only on the affected child and its family but also on the community and the nation at large. To reduce the burden of the society and to reduce the disease incidence by providing genetic counseling, detection of carrier is important. The present study evaluates the role of ‘Naked Eye Single Tube Red Cell Osmotic Fragility Test’ (NESTROFT) in detecting ß-thalassemia trait. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to the study, compared with the control group, all 100 participants in the carrier group showed a positive NESTROFT test with concomitant low values of MCH and MCV making NESTROFT to be a rapid and a reliable method for the detection of thalassaemia trait among our population 18 . Pakistan is one of the highly prevalent countries suffering from inherited haemoglobinopathies, which poses a huge economic burden on the country 2,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study, compared with the control group, all 100 participants in the carrier group showed a positive NESTROFT test with concomitant low values of MCH and MCV making NESTROFT to be a rapid and a reliable method for the detection of thalassaemia trait among our population 18 . Pakistan is one of the highly prevalent countries suffering from inherited haemoglobinopathies, which poses a huge economic burden on the country 2,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Beta Thalassaemia is a group of inherited blood disorders in which the body's ability to produce normal hemoglobin is impaired with reduction in capacity of red blood cells to carry oxygen 1 . Beta thalassaemia is more prevalent in Mediterranean regions, Indian subcontinent, the Middle East, and Southeast Asia 2 .…”
Section: Introductionmentioning
confidence: 99%